Penggunaan Preposisi dalam Tajuk Rencana Harian Riau Pos Edisi November 2020 - Amalia Garnis; Jamilin Tinambunan (UIR Press, 2022)
This research is motivated by the use of prepositions contained in the November 2020 edition of the Riau Pos daily editorial. The use of prepositions in the Riau Pos daily editorial November 2020 edition totals (427) prepositions. The purpose of this study was to determine the use of prepositions in the November 2020 edition of the Riau Pos daily newspaper in the Riau Pos daily newspaper. The theory that is used as a guide in this research is Abdul Chaer (2009). The research method uses a content analysis method with a qualitative approach. The results of this study the authors found 13 uses of prepositions in the editorial of the daily Riau Pos November 2020 edition totaling 427 prepositions. Of the 13 prepositions, the preposition that is more dominant and more widely used in the editorial of the Riau Pos daily November 2020 edition is the preposition where it is, namely the preposition (at). So it can be concluded that the use of prepositions in the Riau Pos daily editorial November 2020 edition is mostly correct and appropriate in its use in filling out the description function in a clause or sentence, but there are still some errors in the use of prepositions, namely the preposition where is (at) in the daily editorial. Riau Pos November 2020 edition.